Modernizacija obrazovanija i nauki v Rossii, Pol'she i Litve: sravnitel'nyj analiz [Modernisation of education and research in Russia, Poland and Lithuania: a comparative analysis] - Simaeva Irina; Kuznetsova Tatyana; Korotkevich Margarita (Балтийский регион, 2011)
This article compares the dynamics, content and character of education system modernization in Russia, Poland, and Lithuania. It is shown that the education systems of Russia, Poland, and Lithuania differ substantially in the secondary and higher education structure, sources of financing, and strategic development directions.